Uncertainties on parton distribution functions from the ZEUS NLO QCD fit to data on deep inelastic scattering - Cooper-Sarkar, A (2002)
An NLO QCD analysis of the ZEUS data on e +p deep inelastic scattering together with fixed-target data has been performed from which the gluon and quark densities of the proton and the value of the strong coupling parameter, α s(M Z2), have been extracted. The study includes a full treatment of the experimental systematic uncertainties, including point-to-point correlations. Different ways of incorporating correlated systematic uncertainties into the fit are discussed and compared.